Primary immunodeficiencies (PID) Life Index in Southeast Asia: A comparative analysis of PID Principles of Care (PoC) - Chan, Chee Mun; Mahlaoui, Nizar; Sánchez−Ramón, Silvia; Pergent, Martine; Solis, Leire; Prevot, Johan; Ali, Adli (Frontiers in Immunology, 2023)
Objective: To analyze the implementation of the Principles of Care (PoC) in primary immunodeficiencies (PID) in Southeast Asia (SEA) countries - six years after its call of action. Methodology: Using the newly developed PID Life Index software, the index of implementation of principles of care in the management of PIDs patients involving the six participating SEA countries (Cambodia, Indonesia, Malaysia, Vietnam, Thailand, and Philippines) were extracted. For each of the six separate principles, the index from the six countries will be compared and presented based on the calculated index. Results: Comparative analysis of the six principles of care of PID in the SEA countries showed low diagnostic rate with minimal availability of diagnostic tests options. Generally, almost all SEA countries provide curative treatments, vaccines, and anti-infectious therapies although the reimbursement scheme varied in relieving patients’ financial burden. We also highlighted the active involvement of patient organizations in SEA, with main areas of work focused on advocacy and increasing awareness among public and healthcare professionals. Discussion and Conclusion: It is applaudable that the SEA continent is gradually strengthening its work in management of PID, especially in Thailand and Vietnam. However, more emphasis must be placed among stakeholders in SEA countries towards successful implementation the PoC for a holistic management of PID patients.